XELOX vs. FOLFOX in metastatic colorectal cancer: An updated meta-analysis. (7th February 2016) - Guo, Yu; Xiong, Bing-Hong; Zhang, Tao; Cheng, Yong; Ma, Li
ABSTRACT: This meta-analysis aims to evaluate chemotherapy with XELOX (capecitabine plus oxaliplatin) versus FOLFOX (fluorouracil plus oxaliplatin) as a treatment for metastatic colorectal cancer (mCRC) in terms of efficacy and safety. Only randomized controlled trials (RCTs) comparing XELOX versus FOLFOX were included. A total of 4, 363 patients from eight RCTs were available for analysis. Pooled analysis revealed that there were no statistical differences between both arms in OS, and ORR. XELOX arm had a higher incidence of thrombocytopenia, hand-foot syndrome, and diarrhea, whereas neutropenia had a higher incidence in the FOLFOX group. For mCRC, the effect of XELOX is similar to FOLFOX.